2020
DOI: 10.1590/1676-0611-bn-2020-1058
|View full text |Cite
|
Sign up to set email alerts
|

Use of highway culverts by the water opossum (Chironectes minimus) in southeastern Brazil

Abstract: The water opossum (Chironectes minimus) is a semi-aquatic mammal that is infrequently sampled in Atlantic rainforest areas in Brazil. Here we report on new records of C. minimus in the state of São Paulo, southeastern Brazil, and comment on its behavior and ecology. We placed nine camera traps in culverts and cattle boxes under a highway, between 2017 and 2019. From a total of 6,750 camera-trap-days, we obtained 16 records of C. minimus (0.24 records/100 camera-trap-days) in two cameras placed in culverts over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(30 reference statements)
0
3
0
2
Order By: Relevance
“…Thus, Galliez et al (2009) suggest that degradation of riparian areas may prevent dispersal to adjacent sub-basin. Furthermore, even the very few studies that registered water opossums in degraded habitats indicated that they were still associated with riverine vegetation (Arias-Alzate et al 2021, Prist et al 2020, Brandão et al 2015. Our record indicates, however, that there are exceptions to this strong association.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…Thus, Galliez et al (2009) suggest that degradation of riparian areas may prevent dispersal to adjacent sub-basin. Furthermore, even the very few studies that registered water opossums in degraded habitats indicated that they were still associated with riverine vegetation (Arias-Alzate et al 2021, Prist et al 2020, Brandão et al 2015. Our record indicates, however, that there are exceptions to this strong association.…”
Section: Resultsmentioning
confidence: 48%
“…However, the water opossum also seems to be able to occur in degraded habitats, with few studies showing that this marsupial is found in degraded riverine forests. Brandão et al (2015) captured an individual in a narrow gallery forest surrounded by monoculture in central Brazil, Prist et al (2020) registered the water opossum in culverts under a highway near a degraded riverine forest in Atlantic Forest biome, and Arias-Alzate et al (2021) described the activity patterns of the water opossum in periurban areas in Colombia. A rapid decline in the potential distribution of the water opossum, however, has been observed, mainly caused by habitat loss and fragmentation (Prieto-Torres & Pinilla-Buitrago 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With the new record, there are now 81 species of bats confirmed to occur in the state of São Paulo (Garbino 2016;Cláudio et al 2020). The western region of São Paulo is one of the least known areas of the state in terms of mammal diversity, and new findings are still being made in the region (Garbino 2016;Prist et al 2020). The fact that there are only a few protected areas and remaining fragments in western São Paulo should make this region a priority area in future assessments (Rezende 2014).…”
Section: Discussionmentioning
confidence: 99%
“…La Chucha de Agua o Perrito de Agua (Chironectes minimus) es quizás uno de los marsupiales menos conocidos a lo largo de su distribución en el Neotrópico (Ojeda et al 2002;Galliez et al 2009;De Souza et al 2013). Su rango geográfico se consideró disyunto (Marshall 1978;Stein & Patton 2007), sin embargo, recientemente se ha propuesto como un rango continuo desde el sur de México hasta el norte de Argentina y el este de Brasil (Prist et al 2020). Es una especie que requiere hábitats bien conservados, en lagos y cursos de agua de bosques tropicales (Marshall 1978;Pérez-Hernández et al 2016;Stein & Patton 2007).…”
Section: Introductionunclassified
“…Asimismo, debido a sus requerimientos ecológicos, este patrón de actividad podría verse alterado por efecto antrópico (Muhly et al 2011;Mendes et al 2020). Por lo que sus principales amenazas son la contaminación de las fuentes de agua, la pérdida de hábitat (Palmeirim et al 2014;Pérez-Hernández et al 2016;Solari & Marín-C 2014) y el atropellamiento en las vías (Coelho et al 2008;Delgado-V 2014;Prist et al 2020).…”
Section: Introductionunclassified